"Trends in MSME Credit Flow in India: A Sectoral and Regional Analysis (2015–2023)" - Savitha H S; Dr. Srivivasa Murthy M D (Educational Administration: Theory and Practice, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in India’s economic development by contributing to employment, innovation, exports, and balanced regional growth. Despite their significance, access to formal credit remains a persistent challenge for this sector. This research paper examines the trends in MSME credit flow across India during the period 2015 to 2023, focusing on both sectoral and regional dimensions. Using descriptive and analytical methods, the study analyzes secondary data from sources such as the RBI, Ministry of MSME, SIDBI, SLBCs, CMIE Prowess, and the Udyam Registration portal. Tools such as trend analysis, CAGR, ratio analysis, correlation, and comparative regional-sectoral assessments are employed to draw meaningful insights. The study finds that while overall MSME credit has grown post-2015, disparities exist in credit distribution across sectors—with a notable shift toward services—and across regions, with southern states being credit-rich compared to northeastern and central regions. The paper also explores the impact of key schemes such as MUDRA, ECLGS, and credit guarantee programs, revealing mixed outcomes in terms of inclusivity and effectiveness. Finally, the paper offers actionable recommendations to improve equitable credit flow and bridge financing gaps in underserved areas and segments.